Involvement of Glycolipid-Enriched Domains in the Transduction Mechanism of Neurotrophins in Cultured Neurons. Issue 5 (October 1999) - Palestini, P.; Masserini, M.; Bottiroli, G.; Brunner, J.; Mutoh, T.; Ferraretto, A.; Ravasi, D.; Pitto, M.
Abstract : Specialized domains, displaying a peculiar lipid and protein composition, are present within the plasma membrane of mammalian cells and play a pivotal role in fundamental membrane-associated events. Among lipids, sphingolipids (in particular glycolipids and sphingomyelin) are characteristically enriched within such domains. Moreover, a series of functionally related proteins is present, suggesting the involvement of these membrane structures in the mechanism of signal transduction and lipid/protein sorting. An increasing body of evidence suggests that domains are dynamic structures, and that their dynamic fluctuations can modulate the activity of domain-associated proteins through changes of glycolipid–protein interaction. Even if a large body of experimental investigation has been carried out on eukaryotic cells, only little attention has been paid to the neuron. The purpose of the present review is to summarize the observations implying a functional role of glycolipid-enriched domains in cultured rat cerebellar granule cells.